The Effect of Personal Selling and Advertising on Purchasing Decisions with Brand Awareness as an Intervening Variable - Pratama, Anugerah Hasfi; Riyanto, Dicky Wisnu Usdek; Kadharpa, Eka (Business Innovation Management and Entrepreneurship Journal, 2023)
This study aims to determine the effect of personal selling on purchasing decisions, the effect of advertising on purchasing decisions, the effect of brand awareness on purchasing decisions, the effect of personal selling on purchasing decisions mediated by brand awareness, and the influence of advertising on purchasing decisions mediated by brand awareness. This research was conducted on My Republic WiFi users in Surabaya with 150 respondents. The sampling technique of this study uses probability sampling using random sampling, in which the researcher determines without regard to the existing strata in the population. Data collection techniques in this study used a questionnaire. Data analysis technique using Process Macro Hayes. The results of this study indicate that the personal selling variable has a significant positive effect on purchasing decisions. Advertising variable has a significant positive effect on purchasing decisions. The brand awareness variable has a positive and significant effect on purchasing decisions. Brand awareness mediates the relationship between personal selling and purchasing decisions. Brand awareness mediates the relationship between advertising and purchasing decisions.